2019
DOI: 10.1111/jfpp.13870
|View full text |Cite
|
Sign up to set email alerts
|

Black and green tea (Camellia sinensis L.) extracts as natural antioxidants in uncured pork sausages

Abstract: The present study evaluated the antioxidant effect of green and black tea (Camellia sinensis L.) extracts in uncured pork sausages. The total polyphenol content in the green tea extract (GTE) was significantly higher (p < 0.05) than the black tea extract (BTE). DPPH assay showed significantly higher (p < 0.05) antioxidant activity in GTE compared to BTE. However, TBARS values of uncured pork sausages significantly reduced (p < 0.05) for all levels of concentrations of BTE (0.05%, 0.10%, 020%, and 0.30%) and GT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 34 publications
4
25
0
Order By: Relevance
“…The incorporation of 1% GTP to lamb sausage resulted in a decrease of lipid oxidation by 40%, 36%, and 38%, respectively during storages in comparison with the control. The results were in line with studies by Bozkurt (2006), Schilling et al (2018), and Jayawardana et al (2019) who reported that green tea extract significantly reduced TBARS values in beef and pork sausages. Qin et al (2013) suggested that the primary mechanism of antioxidants from phenolic compounds in controlling lipid oxidation is mainly due to their capacities in chelating metal ions and trapping reactive oxygen species.…”
Section: Oxidative Stability and Total Plate Countsupporting
confidence: 92%
See 4 more Smart Citations
“…The incorporation of 1% GTP to lamb sausage resulted in a decrease of lipid oxidation by 40%, 36%, and 38%, respectively during storages in comparison with the control. The results were in line with studies by Bozkurt (2006), Schilling et al (2018), and Jayawardana et al (2019) who reported that green tea extract significantly reduced TBARS values in beef and pork sausages. Qin et al (2013) suggested that the primary mechanism of antioxidants from phenolic compounds in controlling lipid oxidation is mainly due to their capacities in chelating metal ions and trapping reactive oxygen species.…”
Section: Oxidative Stability and Total Plate Countsupporting
confidence: 92%
“…The highest water holding capacity was achieved at 14-days of storage. Jayawardana et al (2019) observed no changes with sausages treated by black tea and green tea extract in the levels of 0.05% and 0.30% that measured until 5 d of storage. Similarly, Gai et al (2014) also found that green tea powder did not influence the WHC of meat products.…”
Section: Chemical Composition and Physical Characteristicsmentioning
confidence: 59%
See 3 more Smart Citations